Do arterial resections improve survival in pancreatic cancer?: a narrative review - Gomes dos Santos Ferreira Rebelo, Artur Luis; Ronellenfitsch, Ulrich; Döbereiner, Jessica; Ukkat, Jörg; Kleeff, Jörg H. (Chinese clinical oncology, 2021)
Arterial resection; pancreatic cancer; pancreatic surgery; vascular